Association of eating behavior with symptoms of pelvic floor disorders in middle-aged women: An observational study - Mari A Kuutti; Matti Hyvärinen; Hannamari Lankila; Pauliina Aukee; Enni-Maria Hietavala; Eija K Laakkonen (Women's Health)
Background: Estrogen deficiency during menopause, aging, reproductive history, and factors increasing intra-abdominal pressure may lead to structural and functional failure in the pelvic floor. Lifestyle choices, such as eating behavior, may contribute to pelvic floor disorders. Objectives: The objective of the study was to investigate associations of eating behavior with symptoms of pelvic floor disorders, that is, stress urinary incontinence, urgency urinary incontinence, fecal incontinence, and constipation or defecation difficulties among middle-aged women. Design: A cross-sectional, observational study was performed using a population sample of 1098 Finnish women aged 47–55 years. Methods: Eating behavior, food consumption frequency, demographical, gynecological, and physical activity variables were assessed using self-report questionnaires. Logistic regression models were used to assess the associations of eating behavior, food frequency, and symptoms of pelvic floor disorders. Models were adjusted with demographical, gynecological, and physical activity variables. Results: In adjusted models, middle-aged women with disordered eating style were more likely to experience the symptoms of stress urinary incontinence (odds ratio (OR) 1.5, p  = 0.002), and constipation or defecation difficulties (OR 1.4, p  = 0.041). Adding body mass index into the models abolished associations. Of the studied food items, more frequent consumption of ready-made, highly processed foods (OR 1.5, p  = 0.001), and fast foods (OR 1.5, p  = 0.005) were independently associated with symptoms of stress urinary incontinence regardless of eating style, whereas consuming ready-made foods (OR 1.4, p  = 0.048) was associated with symptoms of urgency urinary incontinence. Daily consumption of fruits (OR 0.8, p  = 0.034) was independently associated with symptoms of stress urinary incontinence. Furthermore, we observed that daily consumption of porridge was associated with symptoms of constipation or defecation difficulties (OR 1.7, p  = 0.010) independently of eating style. Alcohol consumption (OR 0.9, p  = 0.015) was inversely associated with constipation and defecation difficulties. Women with overall higher quality diet had lower odds for stress urinary incontinence (OR 0.9, p  = 0.002). Conclusion: This study provides proof-of-concept evidence to the hypothesis that eating behavior and consuming certain food items are associated with perceived pelvic floor disorders. As a preventive action, eating behavior of women with the risk of these symptoms should be assessed, and guidance toward healthy eating patterns should be provided.